2016
DOI: 10.1186/s12933-016-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of canagliflozin in combination with insulin: a double-blind, randomized, placebo-controlled study in Japanese patients with type 2 diabetes mellitus

Abstract: BackgroundCombination therapy with canagliflozin and insulin was investigated in a prescribed substudy of the canagliflozin Cardiovascular Assessment Study (CANVAS); however, it was not evaluated in Japanese patients with type 2 diabetes mellitus (T2DM). Since the usage profile of insulin therapy and pathologic features of Japanese patients differ from those of Caucasian patients, we determined the clinical benefit of such a combination therapy in Japanese patients.MethodsPatients who had inadequate glycemic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
81
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 37 publications
16
81
4
Order By: Relevance
“…This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations . Adverse events of renal function were infrequent in both treatment groups (2.2% and 3.8% for dapagliflozin and placebo, respectively), and were primarily reported in relation to variation in blood creatinine values in protocol‐mandated regular laboratory checks without clinically symptomatic AEs.…”
Section: Discussionsupporting
confidence: 75%
“…This risk is further increased with the use of SGLT2 inhibitors, likely due to increased glucosuria . The reported incidence of genital infections and UTIs was lower in the present study than in comparable studies in other populations; however, similar results have been reported in other studies of SGLT2 inhibitors in Asian populations . Adverse events of renal function were infrequent in both treatment groups (2.2% and 3.8% for dapagliflozin and placebo, respectively), and were primarily reported in relation to variation in blood creatinine values in protocol‐mandated regular laboratory checks without clinically symptomatic AEs.…”
Section: Discussionsupporting
confidence: 75%
“…Taking these results into account, we guessed that Japanese physicians may be cautious of ADRs potentially caused by SGLT2 inhibitors after the issue of recommendation for SGLT2 inhibitors, resulting in the increase of withdrawal rate due to AEs. All ADRs observed in this survey were already known events that were reported in the previous clinical trials of canagliflozin conducted in Japan [9][10][11][12][13] , and there were no clinically significant concerns in the changes of laboratory variables during our survey period. Recently, the Food and Drug Administration (FDA) and the European Medicines Agency also warned of the risk of ketoacidosis with SGLT2 inhibitors 14 .…”
Section: Discussionmentioning
confidence: 82%
“…20 The drug has been shown to be effective in reducing body weight and improving glycemic control, when used in combination with insulin. 21 Gavin et al (2015) have reported that the drug can provide improved outcomes, such as reduction in HbA1c, body weight and systolic blood pressure in T2DM patients, independent of racial background. 22 Several studies conducted on Indian T2DM patients have also demonstrated the effectiveness of the drug in enabling glycemic control and reducing body weight.…”
Section: Discussionmentioning
confidence: 99%